1975
DOI: 10.1055/s-0028-1091651
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Increased Serum Gamma-Glutamyltransferase Activity during Long-Term Anticonvulsive Treatment. Clinical and Experimental Studies1,2

Abstract: Significance of increased serum gamma-glutamyltransjerase activity during long-term anticonvulsive treatment. Clinical and experimental studies. Neuropadiatrie 6: 77-89 (1975). In epileptic children on anticonvulsive treatment for at least 4 weeks, the following laboratory tests were performed and compared to age matched controls: serum activity determinations of gamma-glutamyltransferase (GGT), alanine (GPT) and aspartate aminotransferases, leucin arylamidase (LAP), alkaline phosphatase (AP), glutamate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In addition there was no sigcn nificant correlation between the percent change in y-glutamyltranspeptidase activity and the per cent change in antipyrine clearance. Serum y-glutamyltranspeptidase in two groups of epileptic children >,, g receiving various anticonvulsant drugs have been -0 reported to be considerably higher than in children v receiving no drug therapy (Bartels et al, 1975;de Park, 1979). Branch & Shand (1979) proposed that >,.j hepatic drug clearance may be regarded as a product of liver size and specific drug metabolising enzyme activity per unit mass of liver and that larger responses to inducing agents would be expected in vindividuals with large livers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition there was no sigcn nificant correlation between the percent change in y-glutamyltranspeptidase activity and the per cent change in antipyrine clearance. Serum y-glutamyltranspeptidase in two groups of epileptic children >,, g receiving various anticonvulsant drugs have been -0 reported to be considerably higher than in children v receiving no drug therapy (Bartels et al, 1975;de Park, 1979). Branch & Shand (1979) proposed that >,.j hepatic drug clearance may be regarded as a product of liver size and specific drug metabolising enzyme activity per unit mass of liver and that larger responses to inducing agents would be expected in vindividuals with large livers.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme induction has also been assessed by measuring changes in the disposition of endogenous compounds. Plasma y-glutamyltranspeptidase (yGT) activity is elevated in groups of young epileptics receiving anticonvulsant drugs (Bartels, et al, 1975;de Wolff et al, 1980) but the influence of CBZ monotherapy on -y-glutamyltranspeptidase activity in individual children is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has previou sl y been sho w n (3,5 -10,28) that antico nvulsive treatment influences the activity of GGT. Several authors reg ard GGT as one indicator of hepatic enzym e induction (3,(5)(6)(7)30) . This enzyme is not specific for the liver, but isoenzyme patterns have suggested that the so urce of serum activities of GGT during a ntico nvulsive treatment is hepatic tissue (9) ; it does not correlate with the activity of alkaline phosphata se (1,26,3 I).…”
Section: Valproic Acidmentioning
confidence: 99%
“…The results indi-Patients on long-term therapy with anticonvulsive drugs may have elevated serum levels of transferases 0-10). During the last decade, debate has focused attention on whether these high enzyme activities are the expression of purely microsomal enzyme induction or of additional liver cell damage [0][1][2][3][4][5]7,8,11), but even morphological studies on small numbers of patients (2,12,13,13a) have not resolved this important clinical problem.We have occasionally observed clinically significant liver disease, although elevated transferases in serum of children receiving anticonvulsive therapy were more common. In addition, increased numbers of cytolysosomes (4) have been found by…”
mentioning
confidence: 99%
See 1 more Smart Citation